Evaluation of holm oak (Quercus ilex) wood as alternative source for cellulose pulp (CELLULOSE CHEMISTRY AND TECHNOLOGY, 2006)
Preservation of forests and increasing environmental awareness have focused research on the exploration of alternative resources for papermaking, a possible source being holm oak wood. The paper reports on the influence of some independent variables in the soda pulping of holm, oak wood \{[\}viz., temperature (135-195 degrees C), operation time (30-90 min) and active alkali concentration (10-20\%)] on the yield, hollocelulose, alpha-cellulose and lignin content, brightness, viscosity and kappa index of the pulps considered. By using a central, composite, factorial design, equations relating each dependent variable to different independent variables were derived, reproducing the experimental results for the dependent variables with errors below 10%. High pulp yield values were obtained under low operating variable conditions. To obtain the best results in brightness, viscosity and kappa index, operation under high values of the independent variables, the kappa index excepted, is necessary. To obtain a suitable value for this parameter, operation at low temperature is recommended. By applying TCF bleaching (A(1)OA(2)ZRP) in pulps obtained under extreme and central conditions of the pulping process, better values for kappa index (3.4) and brightness (83.8 ISO) result for the pulp obtained under maximum operating conditions. Nevertheless, considerable viscosity losses occur under Such conditions.